Metabolic engineering of yeast for improved whole-cell biocatalytic amine production - Seibold,Mikael Ralph (2025)
Saccharomyces cerevisiae has emerged as a versatile platform for whole-cell biocatalysis, owing to its intrinsic regeneration of cofactors and amenability to genetic engineering. However, efficient reductive amination of aromatic carbonyls remains challenging due to competing redox pathways and product inhibition by pyruvate. Building on the redox-rewired TMB4133 strain (∆gpd1,2) that accumulates high levels of cytosolic NADH, we integrated the Chromobacterium violaceum ω-transaminase (Cv-ATA) via chromosomal YIp‐mediated insertion and co-expressed a Bacillus subtilis alanine dehydrogenase (BsAlaDH) using CRISPR–Cas9. Under fully aerobic and reduced-oxygen conditions in Delft medium supplemented with vanillin, the engineered strain achieved complete vanillin conversion within 20 h at high cell density, yielding up to 1.26 mM vanillylamine. Flow-cytometric analysis of a GPD2p-yEGFP3 reporter confirmed sustained NADH overabundance, suggesting a link between elevated redox co-substrate availability and enhanced transamination. In contrast, the control strain with intact GPD1 and GPD2 exhibited minimal vanillylamine formation (<0.4 mM). It also showed impaired ethanol assimilation, indicating that this strain could not be used as a suitable control. These results establish a robust, redox-self-sufficient yeast whole-cell catalyst for vanillin amination that can serve as a platform for further studies into the effect of redox balance on transamination. Future work will focus on anaerobic cultivations, multi-replicate validation, and fed-batch reactor implementation to further boost amine yields.
Keywords: S. cerevisiae; amination; whole-cell bioconversion; metabolic engineering; HPLC; vanillin; vanillylamine; transaminase; applied microbiology